Comparative Law as Basic Research - Hall, Jerome (1980)
This article begins with a critique of the present methods of comparative criminal study. Specifically, the author contends that comparative study often focuses on rules of law, as opposed to their functions. The author suggests that there should be a scientific approach to comparative criminal studies, e.g., the use of his theory of the interrelations of rules, doctrines, and principles ; this satisfies the scientific requirement of system. The author concludes that the subject matter of comparative criminal study should be law-as-action, i.e., action expressing the coalescence of rules of law, values and manifested behavior